Nilai-Nilai Budaya dan Adat Minangkabau dalam Novel Tambo: Sebuah Pertemuan Karya Gus TF Sakai - Aulia Rahmi (Journal on Education, 2023)
Cultural value and custom can’t be separated because custom is part from a culture that inside it there are values that are reflected inside of the life of community or society. One of the novel that describing cultural value and custom is Tambo: Sebuah Pertemuan novel work of Gus Tf Sakai. The aim of this research is to describe Minangkabau cultural values and custom in Tambo: Sebuah Pertemuan novel work of Gus Tf Sakai. The cultural values and custom reviewed based on C.Kluckhohn’s Theory of Antrophology. Approach of this research is qualitative research with content analysis method. Result of the research shows that in novel there are sixteen cultural values from five cultural values orientation: (1) Cultural Values related to human and his life: life based on rules and truth, (2) Cultural values related to human and his works: independence, ingenuity, work by pace, active, and diligent, (3) Cultural Values related to human against time: think for the future, frugality, (4) Cultural values related to human view against nature: maintain harmony with nature and utilizing the nature, (5) Cultural value related to human and others: solidarity, respect, agreement, justice, and obedience. Minangkabau custom that has been found as much as 4 customs, that is (1) custom: custom that truly custom, custom customized, (2) Cupak nan duo: cupak usali (3) undang-undang nan ampek (4) kato nan ampek: kato pusako, kato mufakat, kato dahulu, kato kudian.